2019
DOI: 10.1080/10428194.2019.1646905
|View full text |Cite
|
Sign up to set email alerts
|

Salvage therapy versus upfront autologous stem cell transplantation in multiple myeloma patients with progressive disease after first-line induction therapy

Abstract: It is a matter of debate whether myeloma patients with progressive disease (PD) after induction should receive salvage therapy or proceed directly to autologous stem cell transplantation. We performed a retrospective analysis of 1599 patients treated between 1991 and 2016 at the University Hospital of Heidelberg and other centers. Deepening of response through salvage therapy did not lead to better progression-free or overall survival (PD versus salvage therapy patients:95% CI [0.28, 1.80], p ¼ 0.5 and HR ¼ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The impact of a lack of response to initial treatment on survival outcomes has also been studied in prior cohorts. 11 , 12 , 13 , 17 , 19 , 20 , 21 , 22 However, most of these studies were published before the advent of novel therapies and, thus, did not include patients treated with the current recommendations of triplets/quadruplets as frontline therapy. Our group previously published a series of 816 patients treated mostly with novel agents and found that 17% had primary refractory disease, compared with 6.7% in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of a lack of response to initial treatment on survival outcomes has also been studied in prior cohorts. 11 , 12 , 13 , 17 , 19 , 20 , 21 , 22 However, most of these studies were published before the advent of novel therapies and, thus, did not include patients treated with the current recommendations of triplets/quadruplets as frontline therapy. Our group previously published a series of 816 patients treated mostly with novel agents and found that 17% had primary refractory disease, compared with 6.7% in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Blocka et al found that salvage therapy could be omitted in select patients with PD who were able to undergo transplantation, because no significant PFS and OS benefits were observed when compared with patients who directly underwent transplantation. 22 These patients should not remain off-treatment for prolonged periods, because this has been shown to predict worse outcomes, especially in patients with suboptimal responses to induction. 23 …”
Section: Discussionmentioning
confidence: 99%
“…They focus on a population of patients that failed to achieve a response after first-line induction therapy. A direct comparison is made between salvage therapy prior to transplant and compare this to outcomes in patients that go directly to stem cell transplantation with refractory disease [1]. The authors found that deepening of response with second-line induction therapy prior to stem cell transplantation did not improve progression-free or overall survival and concluded that primary non-responders could go directly to high-dose therapy and stem cell transplantation without compromising their progression free survival.…”
mentioning
confidence: 99%